Seventy-seven clocks eaudiobook Bryant and may series, book 3. - Fowler, Christopher (Bryant & May, 2013)
British sensation author Christopher Fowler pens bestselling crime novels that draw readers into the investigations of Arthur Bryant and John May of Scotland Yard's Peculiar Crimes Unit. Here, an aging attorney becomes the first victim in a series of poisonings that may be the work of a family of cultists.